Improved Mycobacterium tuberculosis clearance after the restoration of IFN‐γ+TNF‐α+CD4+T cells: Impact of PD‐1 inhibition in active tuberculosis patients. Issue 5 (24th March 2020) - Kamboj, Divya; Gupta, Pushpa; Basil, Mandira Varma; Mohan, Anant; Guleria, Randeep; Bhatnagar, Anuj; Mehta, Girija; Kumar, Prabin; Saurabh, Abhinav; Deepak, Rakesh; Thakral, Deepshi; Misra, Pragya; et al.
Abstract: Prolonged therapy, drug toxicity, noncompliance, immune suppression, and alarming emergence of drug resistance necessitate the search for therapeutic vaccine strategies for tuberculosis (TB). Such strategies ought to elicit not only IFN‐γ, but polyfunctional response including TNF‐α, which is essential for protective granuloma formation. Here, we investigated the impact of PD‐1 inhibition in facilitating protective polyfunctional T cells (PFTs), bacillary clearance, and disease resolution. We have observed PD‐1 inhibition preferentially rescued the suppressed PFTs in active tuberculosis patients. In addition, polyfunctional cytokine milieu favored apoptosis of infected MDMs over necrosis with markedly reduced bacillary growth (≪CFU) in our in vitro monocyte‐derived macrophages (MDMs) infection model. Furthermore, the animal study revealed a significant decline in the bacterial burden in the lungs and spleen of infected mice after in vivo administration of α‐PD‐1 along with antitubercular treatment. Our findings suggest that rescuing polyfunctional immune response by PD‐1 inhibition works synergistically with antituberculosis chemotherapy to confer improved control over bacillary growth and dissemination. In summary, our data strongly indicate the therapeutic potential of α‐PD‐1 as adjunct immunotherapy that can rejuvenate suppressed host immunity and enhance the efficacy of candidate therapeutic vaccine(s). Abstract : Flow‐cytometry based phenotypic and functional study of T cell subsets reveals critical role of PD‐1 mediated immune suppression in active tuberculosis patients. Inhibiting PD‐1 may restore protective T cells and facilitate the clearance of Mycobacterium tuberculosis .